Integrating microarray data and single-cell RNA-seq reveals correlation between kit and nmyc in mouse spermatogonia stem cell population - Hashemi Karoii, Danial; Azizi, Hossein; Skutella, Thomas (Frontiers in Cell and Developmental Biology, 2025)
Spermatogonial stem cells (SSCs) are essential for the continuous production of sperm and the maintenance of male fertility. Their selection, culture, and molecular characterization provide critical insights into spermatogenesis and potential therapeutic applications for male infertility. This study utilized CD49f-MACS and matrix selection techniques to isolate SSCs from mouse testicular samples. The molecular profile of the selected SSCs was analyzed through immunocytochemistry, gene ontology enrichment, weighted gene co-expression network analysis (WGCNA), and single-cell RNA sequencing (scRNA-seq). Additionally, protein-protein interaction (PPI) networks were constructed to identify key regulatory factors in SSC maintenance and differentiation. The selected SSCs exhibited a distinct molecular signature, with high expression of Dazl, Pou5f1 (Oct4), Gfra1, Nanog, and Kit. The Kit gene (c-kit) emerged as a crucial regulator of SSC differentiation, strongly associated with retinoic acid (RA)-mediated signaling pathways. Co-expression analysis revealed significant interactions between Kit, Nmyc, and other pluripotency-associated genes, highlighting its role in SSC development. Furthermore, single-cell RNA sequencing confirmed the dynamic expression of Kit during SSC differentiation and early meiosis initiation. Our findings underscore the pivotal role of Kit in spermatogenesis, reinforcing its potential as a therapeutic target for treating male infertility. The study also provides a comprehensive molecular framework for understanding SSC biology, with implications for regenerative medicine, fertility preservation, and in vitro gametogenesis. Further research integrating gene-editing technologies and in vivo models will be essential to explore the full therapeutic potential of SSC-based treatments.